2023
DOI: 10.1101/2023.05.01.538940
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microsporidia dressing up: the spore polaroplast transport through the polar tube and transformation into the sporoplasm membrane

Abstract: Microsporidia are obligate intracellular parasites that infect a wide variety of hosts, including humans. Microsporidian spores possess a unique, highly specialized invasion apparatus involving the polar filament, polaroplast and posterior vacuole. During spore germination, the polar filament is discharged out of the spore forming the hollow polar tube that transports the sporoplasm components including nucleus into the host cell to achieve the invasion. Due to the complicated topological changes occurring in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Some fine fibers were observed on the outermost layer of the polar tubes, which might be the glycosylated PTPs. At the tip of the extruded polar tube of A. algerae, a "J"-shaped hook existed [31,68], which was also found in the extruded polar tube of N. bombycis [70]. During the process of germination, the polar tube first elongated to its maximum length , and then rapidly shortened once the sporoplasm was released [31].…”
Section: Structurementioning
confidence: 90%
See 1 more Smart Citation
“…Some fine fibers were observed on the outermost layer of the polar tubes, which might be the glycosylated PTPs. At the tip of the extruded polar tube of A. algerae, a "J"-shaped hook existed [31,68], which was also found in the extruded polar tube of N. bombycis [70]. During the process of germination, the polar tube first elongated to its maximum length , and then rapidly shortened once the sporoplasm was released [31].…”
Section: Structurementioning
confidence: 90%
“…Live-cell imaging of nuclei transport through the A. algerae polar tube showed that the nuclei were elongated, then recovered a globular shape after exiting the polar tube [31]. Lv et al labeled the diplokaryons of N. bombycis and also found that they were elongated for transport in the polar tube [70]. However, Takvorian et al [68] observed some circular diplokaryons surrounded by a membrane forming the oval or sperm-head-shaped structures in the A. algerae polar tube.…”
Section: Functionmentioning
confidence: 99%
“…These events, including tube eversion and passage of sporoplasm cargo through this constricted tube, are extremely fast and occur within 2 s [ 25 ]. To achieve successful firing, sporoplasm delivery, and host infection, the polar tube and the cargo undergo drastic remodeling during this discharge [ 25 , 27 , 28 ]. These swift ultrastructure changes in the polar tube evince its extraordinary mechanical properties likely conferred by its components, the PTPs.…”
Section: Introductionmentioning
confidence: 99%
“…These swift ultrastructure changes in the polar tube evince its extraordinary mechanical properties likely conferred by its components, the PTPs. However, the mechanisms driving polar tube firing, sporoplasm discharge, and the dynamics of polar tube eversion are not well understood [25,[28][29][30]. Further, the swift nature of germination events creates challenges in capturing polar tube dynamics and contributes to the generally understudied nature of these parasites.…”
Section: Introductionmentioning
confidence: 99%